2018
DOI: 10.1101/475459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Space, time, and captivity: quantifying the factors influencing the fecal microbiome of an alpine ungulate

Abstract: 16The community of microorganisms in the gut is affected by host species, diet, and 17 environment and is linked to normal functioning of the host organism. Although the microbiome 18 fluctuates in response to host demands and environmental changes, there are core groups of 19 microorganisms that remain relatively constant throughout the hosts lifetime. Ruminants are 20 mammals that rely on highly specialized digestive and metabolic modifications, including 21 microbiome adaptations, to persist in extreme envi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Our hypothesis is that some gut bacteria in elephants were replaced by those associated with the other animals in the surrounding environment of captivity. It is worth mentioning that this insignificant difference in alpha diversity between gut microbiome in captive and semi-captive elephants was previously observed by other studies on mammals such as mountain goats 47 and black rhinoceros 48 , which can support our hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Our hypothesis is that some gut bacteria in elephants were replaced by those associated with the other animals in the surrounding environment of captivity. It is worth mentioning that this insignificant difference in alpha diversity between gut microbiome in captive and semi-captive elephants was previously observed by other studies on mammals such as mountain goats 47 and black rhinoceros 48 , which can support our hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the higher bacterial diversity of the captive beetle microbiomes, their microbiomes are more similar to each other in composition compared to the wild beetle microbiomes based on the nMDS ( Figure 3 ). The wild beetle microbiomes individually had lower diversity, but differed more from one another according to the distance between groups in the nMDS, which could be due to increased physical distances between beetles and variation in the environment (Huston & Gibson, 2015, Ajani et al ., 2018, Haworth et al ., 2019). One study found that the gut of captive rhinoceroses has a higher bacterial diversity attributed to contact with humans and interaction with man-made environments (McKenzie et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the host on the rumen microbiome relates to the morphological, physiological, and behavioural adaptations of ruminants to their environmental conditions (Hofmann 1989;Haworth et al 2018). The evolution of the rumen microbiome relative to the host and environment has been reported by Zhang et al (2016).…”
Section: Host Specificity and Rumen Microbial Stabilitymentioning
confidence: 99%